2021
DOI: 10.1111/nmo.14235
|View full text |Cite
|
Sign up to set email alerts
|

Gastric function in diabetic gastroparesis assessed by ultrasound and scintigraphy

Abstract: Background Gastroparesis is a severe diabetes complication characterized by delayed gastric emptying. We examined patients with symptoms of diabetic gastroparesis using gastric emptying scintigraphy and ultrasound drink test. The primary aim was to investigate how ultrasound could provide information about gastric motility features in diabetic gastroparesis. Material and methods We prospectively included 58 patients with diabetes (48 type 1) with symptoms of gastroparesis and 30 healthy controls. Patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Authors concluded that the achievement of glycemic control improves both of gastric motility and gastrointestinal symptoms in patients with diabetic gastroparesis. Consistent with our results, Steinsvik et al [ 30 ] found no significant associations between symptoms of gastroparesis and measurements of ultrasonography in patients with diabetic gastroparesis. In contrast, Darwiche et al [ 31 ] found no significant associations between gastric emptying and the duration of diabetes, HbA1c, age or BMI; these incompatible findings are probably due to their small sample size.…”
Section: Discussionsupporting
confidence: 93%
“…Authors concluded that the achievement of glycemic control improves both of gastric motility and gastrointestinal symptoms in patients with diabetic gastroparesis. Consistent with our results, Steinsvik et al [ 30 ] found no significant associations between symptoms of gastroparesis and measurements of ultrasonography in patients with diabetic gastroparesis. In contrast, Darwiche et al [ 31 ] found no significant associations between gastric emptying and the duration of diabetes, HbA1c, age or BMI; these incompatible findings are probably due to their small sample size.…”
Section: Discussionsupporting
confidence: 93%
“…33 Ultrasonographic studies have documented reduced proximal gastric accommodation and, conversely, antral distension, which was observed to be twice as large in patients with diabetes and gastroparesis compared to healthy controls. 34 However, there were no symptoms significantly associated with the alterations in antral dimensions.…”
Section: Key Pointsmentioning
confidence: 86%
“…Steinsvik et al . [ 13 ] had assessed gastric motility in diabetic patients and proven that good glycaemic control aids in increased antral motility. In the diabetic parturient in this study, the grade 2 antrum might have been secondary to poor glycaemic control.…”
Section: Discussionmentioning
confidence: 99%